The Mathematical Literacy Process Based on The Students' Mathematical Resilience - Setiawan, Agung; ., Wardono; Wijayanti , Kristina; ., Mulyono; Bishtawi , Haneen Omar (Journal of Ecohumanism, 2024)
Mathematical literacy is very important in daily life, however, the mathematical literacy of Indonesian students is still low. Improving mathematical literacy requires a resilient and unyielding attitude known as mathematical resilience. This study aims to find out the process of mathematical literacy reviewed from the mathematical resilience of students. This research uses a qualitative method. The subject of this study is a grade VIII student at one of the junior high schools in Semarang City. Data collection uses questionnaires, written tests, interviews and documentation. Data analysis uses triangulation techniques. The results of the study show that the students' mathematical literacy process has not been optimally achieved against the existing stages of the mathematical literacy process.